2022
DOI: 10.1097/mpa.0000000000002044
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Microcirculatory Disturbances in Acute Pancreatitis

Abstract: Acute pancreatitis is a serious inflammatory condition. Research has shown an increase in the number of pancreatitis-associated hospitalizations, with a marked decline in the mortality rates down to 0.79% in patients with acute pancreatitis and 0.26% in patients with exacerbation of chronic pancreatitis. Up to one-third of patients develop pancreatic tissue necrosis, with a mortality rate of 30%. One of the mechanisms is the disturbances in pancreatic microcirculation due to the release of endothelin, a long-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Compared to CTSI and EPIC, radiomics model had a superior value. It suggested that radiomics features revealed some of the differences between high and low level of disease activity, which was possibly due to some small morphological changes in pancreatic parenchyma caused by hemoconcentration, decreased blood flow, decreased tissue oxygenation decreased, vasoconstriction or increased permeability [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Compared to CTSI and EPIC, radiomics model had a superior value. It suggested that radiomics features revealed some of the differences between high and low level of disease activity, which was possibly due to some small morphological changes in pancreatic parenchyma caused by hemoconcentration, decreased blood flow, decreased tissue oxygenation decreased, vasoconstriction or increased permeability [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of platelet count on intra-abdominal infection is poorly understood, but several explanations could be considered. The inflammatory process results in disturbances in pancreatic microcirculation, which has been recognized as an important factor in the development of acute pancreatitis ( 20 ). The ultra-structural changes in acute pancreatitis, including the infiltration of leukocytes, the accumulation of platelets intravascularly and extravascularly, and the formation of microthrombi, could be observed ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent studies ( 8 , 12 ) have adopted heparin for EUS-guided fine-needle liver biopsy and discovered that heparin prevented the adhesion of tissue strips to the needle tubing wall because of blood coagulation, thus increasing the amount of obtained specimen. A recent study has explored the merits of wet-heparinized pancreas biopsy ( 17 ), but there is currently no data available to explore its effect on the quality of pancreatic specimens. Our study found that the heparin group had longer pancreatic tissue strips than the conventional group (P<0.05), which indicated that the coagulative activity of heparin increased the sample yield in the pancreatic biopsies.…”
Section: Discussionmentioning
confidence: 99%
“…Severe fibrosis in the pancreatic peritumoral tissues can cause the white tissue strips to mingle with segmental fibrotic tissues ( 10 , 17 , 23 ), leading to bias in the MOSE. Therefore, additional laboratory diagnosis is essential.…”
Section: Discussionmentioning
confidence: 99%